On the use of nullator transformation in oscillator circuits - Fongsamut, C.; Anuntahirunrat, K.; Surakampontorn, W.; Fujii, N. (My University, 2006)
A transformation of two nullators for generating a class of current-conveyor-based oscillator circuit that uses two second generation current conveyor (CCIIs), two capacitors and two resistors is proposed. The generating method is through the representation of the nullator-norator equivalents of oscillator circuits. In addition, half of all circuits can be realized by using RC:CR transformation. There are 6 additional circuits of this kind possible that have not been found in the published literature. © 2006 IEEE.